Quality Control Analysis of Fireproof Stone with New Seven Tools Method at PT. Loca Refractories Wira Jatim - Amastasia Cindy Umami; Dwi Sukma Donoriyanto (UNIPA PRESS, 2022)
PT. Loka Refractories Wira Jatim is a manufacturing company that produces refractory stones. In carrying out the production process, defective products are often found. In this study, an analysis of the quality control of refractory stone will be carried out using the New Seven Tools method. The purpose of this study was to determine the quality of refractory stone, the factors that cause disability and the impact. In addition, suggestions for improvements will be given to improve the quality of the refractory stone produced. The results showed that the most common types of defects were 50% in April 2021, while the types of defects that occurred the least were > 1 type of defects as much as 2% in October 2020. The factors causing the formation of defective products include human errors, old machines, undeveloped work methods, and poor quality of raw materials. Improvement activities that can be carried out are improving operator performance, improving machine performance, making work methods, and tightening control of raw materials or QC.